Exposing undergraduate research in institutional repositories - Hall, Robyn (My University, 2017)
Institutional repositories can play an important role in providing students with opportunities to disseminate scholarship, while also acting to highlight and promote undergraduate research activities at academic institutions. Few repositories have fully embraced this role, however. As recent data from a content analysis of Canadian institutional repositories reveals, a majority tend to focus services around disseminating, preserving, and showcasing the work of faculty members, research centres, and graduate students, while largely ignoring undergraduate work. This session will outline effective strategies for attracting attention to undergraduate research in institutional repositories while asserting the benefits of doing so for students and institutions alike. Additionally, participants will learn ways of overcoming challenges related to promoting repository services to undergraduate student populations and obtaining contributions of work, securing rights, and managing deposits. (Poster number 304.)
Presented on June 27, 2017 at the Open Repositories Conference at Queensland University of Technology (QUT) in Brisbane, Australia.
Keywords: undergraduate research; undergraduate theses; institutional repositories; open access